Restrukturisasi Kredit Kepemilikan Rumah Pada Masa Pandemi Covid-19 (Studi Kasus Pada Bank BTN) - Yuniatri Fara Rahmania (Jurist-Diction, 2021)
AbstractCOVID-19 pandemic has affected Indonesia’s economic situation. One of the examples of how COVID-19 affects Indonesia’s economy is the decreasing of debtor capability to finish their obligation in paying credits. Almost all kinds of credits are affected, not to mention the House Ownership Credit. Responding to the situation, Financial Services Authority (FSA) issues a regulation related to the regulation of national economic stimuli during the COVID-19 pandemic and continued by the existence of internal regulation on each bank, as done by Bank Tabungan Negara (Bank BTN) as one of the bank in Indonesia who supports House Ownership Credit movement for Indonesian people.Keywords: Credit; Credit Restructuritation; House Ownership Credit; COVID-19 Pandemic.AbstrakPandemi COVID-19 berimbas pada keadaan perekonomian di Indonesia. Salah satu Contoh imbas COVID-19 pada perekonomian Indonesia yaitu menurunnya kemampuan debitur dalam menyelesaikan kewajibannya dalam melakukan pembayaran Kredit. Hampir seluruh jenis kredit terimbas keadaan tersebut tidak terkecuali Kredit Pemilikan Rumah (KPR). Menanggapi keadaan tersebut, Otoritas Jasa Keuangan (OJK) mengeluarkan peraturan terkait peraturan mengenai stimulus perekonomian nasional pada masa Pandemi COVID-19 dan ditindak lanjuti dengan adanya peraturan Internal pada masing-masing Bank, seperti yang dilakukan oleh Bank Bank Tabungan Negara (Bank BTN) sebagai salah satu bank yang ada di Indonesia yang mendukung pergerakan KPR bagi masyarakat Indonesia.Kata Kunci: Kredit; Restrukturisasi kredit ; Kredit Pemilikan Rumah; Pandemi COVID-19.